2013
DOI: 10.1128/aac.00399-13
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the Activated Rig-I Pathway in Hepatitis C Virus (HCV) Replicon Cells by HCV Protease, Polymerase, and NS5A Inhibitors In Vitro at Clinically Relevant Concentrations

Abstract: Hepatitis C virus (HCV) is a hepatotropic virus that belongs to the family Flaviviridae. Chronic HCV infection can result in fibrosis, cirrhosis, and hepatocellular carcinoma (1). It is estimated that approximately 2% of the world population (ϳ170 million people) is infected with HCV, making it a major world health concern (2-6). The HCV genome consists of a positive-strand RNA molecule of approximately 9,600 nucleotides encoding both structural and nonstructural proteins. Nonstructural proteins 3 (NS3) and 5B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
1
8
0
Order By: Relevance
“…In both DYNAMO 1 and DYNAMO 2, the highest SVR12 rates and lowest incidences of relapse were attained when 24 weeks of treatment with an MCB-containing, four-drug regimen was followed by 24 weeks of peginterferon alfa-2a/ribavirin (administered with BOC in DYNAMO 1). Consistent with in vitro data [ 27 , 28 ], we hypothesize that depletion of the immuno-inhibitory NS3/4A serine protease with DAA-based therapy may restore interferon responsiveness and so explain the higher SVR rates achieved with extended administration of peginterferon alfa/ribavirin in patients previously nonresponsive to this combination [ 29 ]. The inclusion of MCB seemed to diminish HCV subtype-dependent differences in SVR12 rates that have typically been observed in clinical trials of first-generation PI-containing triple therapy regimens [ 10 , 11 , 30 ].…”
Section: Discussionsupporting
confidence: 81%
“…In both DYNAMO 1 and DYNAMO 2, the highest SVR12 rates and lowest incidences of relapse were attained when 24 weeks of treatment with an MCB-containing, four-drug regimen was followed by 24 weeks of peginterferon alfa-2a/ribavirin (administered with BOC in DYNAMO 1). Consistent with in vitro data [ 27 , 28 ], we hypothesize that depletion of the immuno-inhibitory NS3/4A serine protease with DAA-based therapy may restore interferon responsiveness and so explain the higher SVR rates achieved with extended administration of peginterferon alfa/ribavirin in patients previously nonresponsive to this combination [ 29 ]. The inclusion of MCB seemed to diminish HCV subtype-dependent differences in SVR12 rates that have typically been observed in clinical trials of first-generation PI-containing triple therapy regimens [ 10 , 11 , 30 ].…”
Section: Discussionsupporting
confidence: 81%
“…Indeed, Kalkeri et al . showed that PIs including telaprevir, boceprevir, and simeprevir can restore innate immunity by directly inhibiting NS3/4A protease-mediated cleavage of MAVS at clinically achievement concentrations in vitro using HCV replicon cells [ 25 ]. Therefore, in PEG-IFN/RBV/PI therapy, the expression of ISGs, IFN-λs, and molecules related to the innate immune system may be more markedly altered early after the start of this therapy than PEG-IFN/RBV therapy without PI.…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies have demonstrated that small-molecule inhibition of NS3 can restore host cell innate immune signaling by preventing the cleavage of MAVS (4,5). Kinetic analyses demonstrated that restoration of signaling was faster with a protease inhibitor (2 to 4 days, depending upon the concentration) than with a polymerase inhibitor (7 days) (4).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NS3 cleaves the adaptor proteins MAVS (2) and TRIF (3) to block activation of interferon gene expression through the retinoic acidinducible gene I (RIG-I) and Toll-like receptor 3 (TLR3) pathways. Thus, the NS3 protease is a particularly attractive target for antiviral intervention since its inhibition not only interferes with polyprotein processing but also restores antiviral signaling (4,5). The first direct-acting antiviral drugs to be approved for the therapy of chronic hepatitis C, boceprevir (6) and telaprevir (7), are both peptidomimetic linear ketoamides that target the active site of the protease domain of NS3.…”
mentioning
confidence: 99%